Identification and characterization of pathogenicity-related genes of Rhizoctonia solani AG3 during tobacco infection - Tang, Qianjun; Ma, Qianqian; Xiao, Zhipeng; Xiao, Yansong; Wang, Yunsheng; Liu, Lei; Peng, Weiye; Wang, Bing; Liu, Tianbo; Song, Na (Frontiers in Plant Science, 2023)
Tobacco target spot disease is caused by a ubiquitous soil-borne phytopathogen Rhizoctonia solani; the pathogenic mechanisms underlying the effects of R. solani remain unclear. Deeper understanding of the functional responses to R. solani during host plant infection would help identify the molecular mechanisms essential for successful host invasion. In this study, we performed global transcriptional analysis of R. solani during various stages (12, 24, 48, 72, 96, and 120 h) of tobacco infection via an RNA sequencing method, while utilizing the pathosystem model R. solani AG3–tobacco (Nicotiana tabacum L.). After R. solani inoculation, the number of differentially expressed genes of R. solani differed at the various time points. Moreover, several gene ontology and Kyoto encyclopedia of genes and genomes pathways were unique in different infection stages, especially with respect to the genes involved in plant cell wall degradation and catalysis of biotransformation reactions, such as the pectin metabolic process and pectin catabolic process. In addition, we found that large amounts of reactive oxygen species were generated after R. solani inoculation and R. solani encoding FAD/NAD binding oxidoreductase (FNBO) and peroxidase gene family to eliminating ROS and counteract oxidative stress.Overall, our findings show that pectin-degrading enzymes and cytochrome P450 genes are critical for plant infection. To our knowledge, our results provide comprehensive insights into R. solani AG3 transcriptome responses during tobacco invasion.